The Poetics of Tajik Cinema - Arabova, Sharofat (Journal of religion and popular culture, 2021)
This study aims to examine the poetics of the representation of Muslim culture, and, more generally, the worldview portrayed in a number of prominent Tajik films of both the Soviet and post-Soviet periods, and thus to determine the trends affecting the development of Tajik cinema in the early twenty-first century. With examples from selected films, cultural practices, and theatrical forms and traditions, the author distinguishes the salient features of the cinema of Tajikistan, including social normativity, spiritual escapism, the edifying nature of the films, and the thematic restriction meant to preserve traditional Muslim values.